2013
DOI: 10.5792/ksrr.2013.25.4.194
|View full text |Cite
|
Sign up to set email alerts
|

Navigation-Assisted Total Knee Arthroplasty for Patients with Extra-Articular Deformity

Abstract: PurposeSince the existence of an extra-articular deformity seriously alters the normal geometry and kinetics around the knee joint, difficulties are often encountered in total knee arthroplasty (TKA) using a standard surgical technique. The purpose of this study was to evaluate the usefulness of surgical navigation system as a treatment option for osteoarthritic knees with extra-articular deformity.Materials and MethodsThe authors retrospectively reviewed medical records of the patients who underwent primary T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Summary of published literature on TKA in extra-articular deformity is presened in Table 3 and 4. Table 3 Outcomes of TKA in bone deformity using computer navigation and neglecting extra-articular deformity Authors Calvin et al [10] Chou иet al [11] Liu et al [12] Mullaji et al [13] Rhee et al [14] Shao et al [15] Tigani et al [16] Bottros et al [17] Klein et al [18] Catani et al [19] Year FS functional score; HTO high tibial osteotomy. Table 4 Outcomes of TKA combined with corrective osteotomy Deschamps и соавт.…”
Section: Resultsmentioning
confidence: 99%
“…Summary of published literature on TKA in extra-articular deformity is presened in Table 3 and 4. Table 3 Outcomes of TKA in bone deformity using computer navigation and neglecting extra-articular deformity Authors Calvin et al [10] Chou иet al [11] Liu et al [12] Mullaji et al [13] Rhee et al [14] Shao et al [15] Tigani et al [16] Bottros et al [17] Klein et al [18] Catani et al [19] Year FS functional score; HTO high tibial osteotomy. Table 4 Outcomes of TKA combined with corrective osteotomy Deschamps и соавт.…”
Section: Resultsmentioning
confidence: 99%
“…According to the forecast of Gartner Inc. MIS of the 4th generation should have been implemented and MIS of the 5th generation should have appeared by 2016. In Russia among the most popular preoperative planning systems, which by its functionality are beyond the scope of the requirements imposed on the MIS 1st, 2nd and 3rd generation are: TraumaCAD [4][5][6][7], MediCAD (http://www.hectec.de/content/index.php/us), OrthoView [8][9][10], Sectra AB (http://www.sectra.com/medical/osteoporosis/index.html), Surgimap [11,12] IMPAX orthopedic instruments (http://www.agfahealthcare.com). The aim of this study is the identification of the key challenges arising during the implementation of the preoperative planning systems in the practice of spine surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Authors reported their immediate postoperative alignment by IAC with various system including computer assisted navigation (Klein et al [12] , Hamada et al [13] , Catani et al [14] , Tigani et al [9] , Rhee et al [5] , Bottros et al [15] ), Extra Medullary Jig guidance (Wang et al [16] ), Patient Specific Instrumentation (Thienpont et al [17] ). All the studies reported post-operative alignment between 0.2*-1.5*.…”
Section: Intra Articular Correctionmentioning
confidence: 99%
“…Eleven studies where case reports. Three where level -IV, and case series studies Extra atricular deformity Extra articular deformity is defined as one with preoperative radiograph showing uniplanar or multiplanar deformity in shaft of femur or tibia resulting in gross alteration of limb neutral mechanical axis leads to secondary osteoarthritis of knee joint [5] . Most of the extra articular deformity in review results from previous fracture malunion.…”
Section: Should All the Deformity Be Corrected?mentioning
confidence: 99%